Mice with Spontaneous Mammary Tumors Develop Type-Specific Neutralizing and Cytotoxic Antibodies Against the Mouse Mammary Tumor Virus Envelope Protein gp52 - Schochetman, Gerald (1979)
Sera from C3H mammary tumor-bearing mice contain cytotoxic antibodies for mouse mammary tumor virus (MMTV)-producing cells, based on (51)Cr release in a complement-dependent serum cytotoxicity assay. The cytotoxic antibodies could be absorbed by purified C3H MMTV gp52 and C3H MMTV-infected cat cells (C3H [MMTV] CrFK) containing cell surface MMTV gp52. However, purified MMTV p27 and uninfected CrFK cat cells were negative. Absorption of the sera with GR (MMTV) CrFK cells also removed all of the cytotoxicity, whereas absorption with RIII (MMTV) CrFK cells was negative, even though all three infected cat cells contained equivalent amounts of gp52. The same C3H cytotoxic sera also neutralized the focus-forming capacity of a C3H MMTV pseudotype of Kirsten sarcoma virus containing MMTV gp52. In contrast, sera from mammary tumor-bearing GR and RIII mice did not neutralize the pseudotype. Furthermore, neutralization could be achieved only by anti-gp52 but not by anti-gp36, -p27, -p14, or -p10 C3H MMTV sera. The gp52's of C3H, GR, and RIII MMTV could also be distinguished by using a type-specific competition radioimmunoassay employing (125)I-gp52 of C3H MMTV and a hyperimmune rabbit anti-C3H MMTV serum. To demonstrate these differences directly, we studied the primary structure of gp52 on the surface of the C3H, GR, and RIII (MMTV) CrFK cells. Two-dimensional tryptic peptide maps of the cell surface lactoper-oxidase-catalyzed iodinated gp52's revealed a greater number of peptides common to the gp52's of C3H and GR MMTVs than to RIII MMTV gp52. These results demonstrate that gp52 is a major target antigen for both cytotoxic and neutralizing antibodies, that the cell surface and virion-associated gp52's of C3H, GR, and RIII MMTV contain both group- and type-specific determinants, and that C3H and GR MMTV gp52's are antigenically more related to each other than to RIII MMTV gp52. Furthermore, C3H mammary tumor-bearing mice develop type-specific antibodies capable of recognizing unique gp52 determinants and, therefore, are able to distinguish the gp52 of C3H MMTV from the gp52's of GR and RIII MMTV.